Front Matter - Cunha, Mônica Ximenes C. da; Souza Júnior, Marcílio F. de; Marques, Johnny C.; Classe, Tadeu M. de; Araújo, Rafael D. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Front Matter SBSI 2023.